The Promise of Religious Naturalism - Hogue, Michael S. (Rowman & Littlefield Publishers, 2010)
The Promise of Religious Naturalism explores religious naturalism as a distinctly promising form of contemporary religious ethics. Examining how religious naturalism responds to the challenges of recent religious transformations and ecological peril worldwide, author Michael Hogue argues that religious naturalism is emerging as an increasingly plausible and potentially rewarding form of religious moral life. Beginning with an introduction of religious naturalism in the larger context of religious and ethical theories, the book undertakes the first extended study of the works of religious naturalists Loyal Rue, Donald Crosby, Jerome Stone, and Ursula Goodenough. Hogue pays particular attention to the ethical components of religious naturalism in relation to religious pluralism and ecological issues.